Acid Rain Management Digitalization Within Environmental Economics - Eugene P. ISTOMIN; Valery M. ABRAMOV; Oksana PETRIEVA; Vyacheslav G. BURLOV; Evgeniy A. BAIKOV; Vladimir A. BOLSHAKOV; Yaroslav A. PETROV; Mikhail B. SHILIN; Elena S. NOVOZHILOVA; Vladimir N. ZAVGORODNIY (Communications of International Proceedings, 2021)
In article, presented development results for digitalization of acid rain management under climate change and COVID-19 pandemic. The authors used situational analysis, Foresight technologies, risk management approach, web technologies and methods of building databases in distributed networks. As result, remote sensing and supercomputer simulation data was recommended to improve the efficiency and reliability of acid rain management. As essential research result, it was proposed to use aggregated modular decision aid instrument, which integrate heterogeneous resources within distributed networks. As study results, there were demonstrated examples of developed aggregated modular decision aid instrument using. The presented in article research results have significant scientific novelty and can be useful for different market players. Platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for data exchange and discussion while the study.
Keywords: digitalization; acid rain management; decision aid; climate change.